2021
DOI: 10.3390/molecules26165006
|View full text |Cite
|
Sign up to set email alerts
|

Comparative and Combinatorial Effects of Resveratrol and Sacubitril/Valsartan alongside Valsartan on Cardiac Remodeling and Dysfunction in MI-Induced Rats

Abstract: The development and progression of heart failure (HF) due to myocardial infarction (MI) is a major concern even with current optimal therapy. Resveratrol is a plant polyphenol with cardioprotective properties. Sacubitril/valsartan is known to be beneficial in chronic HF patients. In this study, we investigated the comparative and combinatorial benefits of resveratrol with sacubitril/valsartan alongside an active comparator valsartan in MI-induced male Sprague Dawley rats. MI-induced and sham-operated animals r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Some clinical trials also indicated the emerging role of Sacubitril/Valsartan in MI patients. Many preclinical experiments have confirmed the cardioprotective role of Sacubitril/Valsartan in MI and explored the underlying mechanisms [14][15][16][17]. In rabbit MI models, Sacubitril/Valsartan treatment offered better short-term and long-term benefits of preventing left ventricular dysfunction compared with valsartan [18].…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical trials also indicated the emerging role of Sacubitril/Valsartan in MI patients. Many preclinical experiments have confirmed the cardioprotective role of Sacubitril/Valsartan in MI and explored the underlying mechanisms [14][15][16][17]. In rabbit MI models, Sacubitril/Valsartan treatment offered better short-term and long-term benefits of preventing left ventricular dysfunction compared with valsartan [18].…”
Section: Discussionmentioning
confidence: 99%
“…Together with ACEI, ARNI sacubitril/valsartan suppresses cardiac dysfunction and fibrosis via the downregulation of TGF-β1, BNP, α-SMA, vimentin ( Liu et al, 2021b ). Furthermore, valsartan and sacubitril/valsartan prevent adverse remodeling in MI rats by reducing oxidative stress, inflammation, and fibrosis ( Raj et al, 2021 ). In MI with hypertensive rats model, the mineralocorticoid receptor antagonist (MRA) spironolactone reduces CFs, MFs, and macrophages infiltration in the heart and kidney ( Leader et al, 2021 ); however, it also binds other steroid receptors (e.g., progesterone and androgen receptors) causing side effects (e.g., gynecomastia and galactorrhea) ( Weldon and Brown, 2019 ).…”
Section: Interventions For Cardiac Fibrosismentioning
confidence: 99%
“…Oxidative stress and inflammation are the culprits in almost all diseases including heart failure. Sacubitril/valsartan mitigates oxidative stress and inflammation in vivo ( Yang et al, 2019 ; Raj et al, 2021 ) and in vitro ( Peng et al, 2020 ) models of heart failure as well as in patients with the disease ( Acanfora et al, 2020 ; Bunsawat et al, 2021 ; Pang et al, 2021 ). The drug diminished production of intracellular reactive oxygen species (ROS), oxidative products such as malondialdehyde, and inflammatory factors (tumor necrosis factor-α, TNF-α; interleukins IL-6 and IL-1β) in the models.…”
Section: Mechanistic Roles Of Sacubitril/valsartan In Cardiac Remodelingmentioning
confidence: 99%
“…Therapy with sacubitril/valsartan was shown to improve Tei index (Gokhroo et al, 2021) and global longitudinal strain in heart failure patients (Valentim Gonçalves et al, 2019;Valentim Gonçalves et al, 2020a;Mirić et al, 2021). In addition, sacubitril/valsartan improves fractional shortening, cardiac output, loaddependent indices of left ventricular contractility (dp/dt max ), and relaxation (dp/dt min ) in animal heart failure models (Maslov et al, 2019b;Ge et al, 2020;Liu Y. et al, 2021;Raj et al, 2021) (Table 2). Combination therapy of sacubitril/valsartan therapy with SGLT2 inhibitors-originally developed as anti-diabetic drugs-has shown additional benefits in patients with diabetic cardiomyopathy (Kim et al, 2021;Karabulut et al, 2022).…”
Section: Effects On Cardiac Functionmentioning
confidence: 99%